Expression of lipoprotein lipase mRNA and secretion in macrophages isolated from human atherosclerotic aorta. - Mattsson, L (1993)
The expression of lipoprotein lipase (LPL) mRNA and the LPL activity were studied in macrophages (CD14 positive) from human atherosclerotic tissue. Macrophages were isolated after collagenase digestion by immunomagnetic isolation. About 90% of the cells were foam cells with oil red O positive lipid droplets. To analyze the mRNA expression, PCR with specific primers for LPL was used. Arterial macrophages were analyzed directly after isolation and the data showed low expression of LPL mRNA when compared with monocyte-derived macrophages. To induce the expression of LPL mRNA in macrophages, PMA was used. When incubating arterial macrophages with PMA for 24 h we could not detect any increase in LPL mRNA levels. Similarly, the cells secreted very small amounts of LPL even after PMA stimulation. In conclusion, these studies show a very low expression of LPL mRNA in the CD14-positive macrophage-derived foam cells isolated from human atherosclerotic tissue. These data suggest that the CD14-positive cells are a subpopulation of foam cells that express low levels of lipoprotein lipase, and the lipid content could be a major factor for downregulation of LPL. However, the cells were isolated from advanced atherosclerotic lesions, and these findings may not reflect the situation in early fatty streaks.